Penguatan Pendidikan Karakter Melalui Program Pembiasaan Membaca Asmaul Husna di SDN Wonotingal - Tafrikhatul, Delaga; Listyarini, Ikha; Irianto, Bernardus (JURNAL SINEKTIK, 2025)
This study aims to determine the Asmaul Husna reading habituation program that strengthens students' character education at Wonotingal Elementary School. This type of research uses descriptive qualitative methods with phenomenological research. Data collection methods were carried out using interviews, observation, and documentation. While the data analysis techniques are data reduction, data presentation, and conclusion drawing, The results of this study found that strengthening character education through the asmaul husna reading habituation program, which is attended by all students and teachers who are Muslim, is carried out every Wednesday from 07.00 WIB until 08.00 WIB, ending with art performance activities or showing off for students. This can make the personalities of students good, positive, disciplined, creative, religious, honest, tolerance, curiosity, friendly and communicative, care for the environment, and responsible.